OC-002 Circulating Dendritic Cell Subsets in Crohn's Disease Show Alterations in Tissue Homing and Cytokine Production. (17th August 2016) - Hendy, PA; Reddi, D; Barnardo, D; Durant, L; Noble, A; Bhat, P; English, N; Knight, SC; Hart, AL
Abstract : Introduction: Crohn's disease (CD) is characterised by an exaggerated immune response to mucosal antigen. Dendritic cells (DC) are the primary antigen presenting cells and may promote either tolerogenic or inflammatory T cell responses to mucosal antigens. We characterised homing marker profile and ongoing cytokine production of circulating DC subsets from patients with Crohn's disease. Methods: DC within peripheral blood mononuclear cells from adults with active luminal Crohn's or from healthy controls (HC) were characterised using flow cytometry. DC were identified as HLA-DR + and negative for markers of other cell lineages (CD3, CD14, CD16, CD19, CD34). Myeloid DC (mDC, CD11c + CD123 − ) and plasmacytoid DC (pDC, CD11c − CD123 + ) were assessed for phenotype (maturation status, homing markers and pattern recognition receptors) and on-going cytokine production by surface and intracellular staining, respectively. Results: In patients with Crohn's (n = 16), a greater proportion of myeloid DC expressed a gut-homing profile (CLA − β7 +, p = 0.0022) compared to controls (n = 10) where most myeloid DC were not tissue-specific (CLA + β7 +, p = 0.0014, Fig C). In Crohn's and controls, myeloid DC were largely gut-homing (CLA − β7 +, p = 0.003) whilst plasmacytoid DC were strongly skin (CLA + β7 − ) and lymph node (CCR7 + ) homing (p < 0.0001 e.g. Fig D). Production of pro-inflammatory cytokines was up-regulated in Crohn's, with myeloid DC producing higher levels of TNFα (p = 0.0042, Fig A) and plasmacytoid DC producing higher levels of IL-6 (p = 0.013, Fig B). Expression of maturation marker CD86 was increased on myeloid DC in Crohn's but not on plasmacytoid DC (p = 0.027 and p = 0.13 respectively). Expression of IFN-α, Il-1β, Il-12, CD40, CD80, TLR2 and TLR4 on DC were not different between Crohn's and controls for either DC subset. Conclusion: The increased myeloid DC expression of gut homing phenotype markers and production of TNFα in Crohn's compared with controls highlights the central role that DC play in the pathogenesis of Crohn's disease. Differences between homing markers on myeloid DC (gut homing) and plasmacytoid DC (skin homing) suggest that they may have different roles in different manifestations of Crohn's, with myeloid DC being central to gut inflammation whilst plasmacytoid DC might be involved in cutaneous Crohn's disease and the skin sequelae of anti-TNFα therapy. Disclosure of Interest: None Declared